Managing a better school - Potter, David; Powell, Graham (Melbourne : Heinemann educational, 1992)
Based on a rationale for planning, development and school improvement, this book presents recent research on how efficient schools work. It suggests how to explore a school's behaviour and performance, and advises on how to plan coherently for improvement across the board.
Keywords: School management and organization -- Great Britain; School management and organization -- Great Britain